PS204 Losses of Long-Range Correlation in the Heart Rate Variability of Patients With Chagas’ Disease - Irurzun, Isabel Maria (2016)
Parasympathetic dysautonomia is an established feature of Chagas disease, but its early detection is still challenging. In a previous work we have developed the index FNNF10 based on the non-linear characteristics of the heart rate variability (HRV). We have tested it on about 500 subjects with different cardiac diseases and found that FNNF10 is sensitive to parasympathetic-sympathetic balance alterations. In the present work we show that Chagasic patients without clinical findings of disease have values of FNNF10 higher than healthy subjects. We also show that FNNF10 potentially depends on the individual age.